The engine of the reef: photobiology of the coral–algal symbiosis - Roth, Melissa S. (Frontiers in Microbiology, 2014)
Coral reef ecosystems thrive in tropical oligotrophic oceans because of the relationship between corals and endosymbiotic dinoflagellate algae called Symbiodinium. Symbiodinium convert sunlight and carbon dioxide into organic carbon and oxygen to fuel coral growth and calcification, creating habitat for these diverse and productive ecosystems. Light is thus a key regulating factor shaping the productivity, physiology and ecology of the coral holobiont. Similar to all oxygenic photoautotrophs, Symbiodinium must safely harvest sunlight for photosynthesis and dissipate excess energy to prevent oxidative stress. Oxidative stress is caused by environmental stressors such as those associated with global climate change, and ultimately leads to breakdown of the coral-algal symbiosis known as coral bleaching. Recently, large-scale coral bleaching events have become pervasive and frequent threatening and endangering coral reefs. Because the coral-algal symbiosis is the biological engine producing the reef, the future of coral reef ecosystems depends on the ecophysiology of the symbiosis. This review examines the photobiology of the coral-algal symbiosis with particular focus on the photophysiological responses and timescales of corals and Symbiodinium. Additionally, this review summarizes the light environment and its dynamics, the vulnerability of the symbiosis to oxidative stress, the abiotic and biotic factors influencing photosynthesis, the diversity of the coral-algal symbiosis and recent advances in the field. Studies integrating physiology with the developing “omics” fields will provide new insights into the coral-algal symbiosis. Greater physiological and ecological understanding of the coral-algal symbiosis is needed for protection and conservation of coral reefs.